1998
DOI: 10.1007/s004310050845
|View full text |Cite
|
Sign up to set email alerts
|

Social class and obesity in 12-year-old children in Brussels: Influence of gender and ethnic origin

Abstract: From early adolescence on, social inequality influences the prevalence of obesity in Belgian girls, but not in Belgian boys nor in immigrant children. Prevention of obesity should take into account the influence of gender, social class and ethnic origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 24 publications
4
17
0
2
Order By: Relevance
“…The higher prevalence of obesity in subjects with a lower social status is in line with other Belgian studies (De Spiegelaere et al 1998;StamMoraga et al 1999). Based on school health fi les of 2 607 children, social inequality -based on parents' professions and the status of their activity -in the prevalence of obesity in Belgian girls was found (De Spiegelaere et al 1998). A similar conclusion was found in adults, based on the Belgian Interuniversity Research on Nutrition and Health.…”
Section: Discussionsupporting
confidence: 80%
“…The higher prevalence of obesity in subjects with a lower social status is in line with other Belgian studies (De Spiegelaere et al 1998;StamMoraga et al 1999). Based on school health fi les of 2 607 children, social inequality -based on parents' professions and the status of their activity -in the prevalence of obesity in Belgian girls was found (De Spiegelaere et al 1998). A similar conclusion was found in adults, based on the Belgian Interuniversity Research on Nutrition and Health.…”
Section: Discussionsupporting
confidence: 80%
“…Results are similar to those observed in our study. In Belgian children aged 12 years, it has been ob- served that in girls, the lower their social class, the higher was the prevalence and severity of obesity; there was no such signifi cant relationship among boys [29] . In Germany, Langnäse et al [30] observed, in a group of 5-to 7-year-old children, an inverse social gradient.…”
Section: Discussionmentioning
confidence: 99%
“…In Belgian children aged 12 y, it has been observed that, in girls, the lower their social class, the higher was the prevalence and severity of obesity; there was no such significant relationship in boys. 17 In Germany, Langnäse et al 18 have observed, in a group of 5-7-y-old children, an inverse social gradient. The ORs for overweight (low vs high social class) reached 3.1 in boys and 2.3 in girls.…”
Section: Socio-demographic Determinantsmentioning
confidence: 99%